Formulation of novel screen-printable dielectric ink for fully-printed TIPs-pentacene OFETs - Hou, Xiaoya (2016)
Polymer nanocomposite dielectric inks based on P(VDF-TrFE)/PMMA/BaTiO3/silica were formulated for screen printing. GPTMS-modified BaTiO3 was incorporated to improve their dielectric properties and fumed silica to achieve good printability of the dielectric inks. Fully-printed TIPs-pentacene OFETs were successfully fabricated using the optimized dielectric ink with 52% BaTiO3 loading.